Membangun Gen-Z yang Berbudaya dengan Berkain-Berkebaya di Kampus UWM Yogyakarta - Dyaloka Puspita Ningrum (Jurnal Surya Masyarakat, 2025)
The acceleration of foreign culture has indeed marginalized many people's old habits which are synonymous with the meaning of wisdom, one of which is the use of regional clothing "Kain and Kebaya" in the context of everyday life. Even though the kebaya is national clothing as stated in Presidential Decree Number 18 of 1972 concerning Types of Civil Clothing and Law Number 9 of 2010 concerning Protocols. Looking at the use of kebaya by Indonesian women today, it tends to be found only at a few formal events. As is the case with the beauty of various Indonesian fabrics which are also becoming increasingly distant from modern society. Apart from the massive onslaught of fashion trends from the international world, this continues to be another factor, especially for the younger generation. The target group for this activity is Gen-Z who are 18-25 years old and are academics at Widya Mataram University, Yogyakarta, as well as several external guests who come from the Yogyakarta area. This activity uses talk-show, question-answer and interactive simulation methods among invited guests. The contents of the activities include: (1) Indonesian fabric exhibition "Javanese Batik Art Culture, (2) fashion show (3) talk show with the title "Contemporary Culture Vs Local Culture from the Perspective of Young People", as well as "Young People's Appreciation in Building Fabric Fashion Trends Dressing", and (4) a culinary bazaar which was enlivened by a number of local MSME players. Gen-Z is invited to collaborate on social media to popularize traditional clothing. In fact, all the invited guests looked very enthusiastic and expressive following the activities by appearing using the dress code "Kebaya", "Batik", "Regional Cloth", as well as other local cultural attributes with their own colors, motifs and aesthetic values.